2019
DOI: 10.1002/ange.201900773
|View full text |Cite
|
Sign up to set email alerts
|

Solid Base Bi24O31Br10(OH)δ with Active Lattice Oxygen for the Efficient Photo‐Oxidation of Primary Alcohols to Aldehydes

Abstract: The selective oxidation of primary alcohols to aldehydes by O2 instead of stoichiometric oxidants (for example, MnVII, CrVI, and OsIV) is an important but challenging process. Most heterogeneous catalytic systems (thermal and photocatalysis) require noble metals or harsh reaction conditions. Here we show that the Bi24O31Br10(OH)δ photocatalyst is very efficient in the selective oxidation of a series of aliphatic (carbon chain from C1 to C10) and aromatic alcohols to their corresponding aldehydes/ketones under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The donated protons further accept the conduction band electrons to generate metastable Hads under irradiation, which can then be rapidly scavenged by hydrogen acceptors (A) to form valuable organic compounds, rather than H2 gas. Moreover, joint utilization of basic surface sites and active lattice oxygen in Bi24O31Br10(OH)δ is a promising way to selectively oxidize aliphatic and aromatic alcohols to the corresponding aldehydes/ketones due to boosted dehydrogenation in photooxidation of alcohols 1194 . Defect engineering in LDHs also play a vital role in the hydroxylation of benzene 1195 , selective oxidation of aromatic alcohols 1196 , and hydroxylation of phenol 1197 .…”
Section: Photocatalytic Organic Synthesismentioning
confidence: 99%
“…The donated protons further accept the conduction band electrons to generate metastable Hads under irradiation, which can then be rapidly scavenged by hydrogen acceptors (A) to form valuable organic compounds, rather than H2 gas. Moreover, joint utilization of basic surface sites and active lattice oxygen in Bi24O31Br10(OH)δ is a promising way to selectively oxidize aliphatic and aromatic alcohols to the corresponding aldehydes/ketones due to boosted dehydrogenation in photooxidation of alcohols 1194 . Defect engineering in LDHs also play a vital role in the hydroxylation of benzene 1195 , selective oxidation of aromatic alcohols 1196 , and hydroxylation of phenol 1197 .…”
Section: Photocatalytic Organic Synthesismentioning
confidence: 99%
“…For example, benzyl alcohol was photocatalytically oxidized to benzaldehyde using Bi 12 O 17 Cl 2 , 123 whereby charge separation and superoxide production by photogenerated electrons synergistically enhanced the selectivity to 99% and yield to 44%. In another typical study, modified Bi 24 O 31 Br 10 (OH) x was used to aid converting primary alcohols to the corresponding aldehydes, 125 showing a quantum efficiency of isopropanol of 71% at 450 nm irradiation in 24 h. These studies replaced expensive noble metal-based oxidation reactions systems with clean photooxidations; some findings are listed in Table 1.…”
Section: Photocatalytic Applications Of Bioxmentioning
confidence: 99%
“…Sabaté can selectively oxidize primary alcohols to aldehydes under visible light irradiation at room temperature using air. 301 The XPS analysis of the O1s spectra reveals that O L is converted to the adsorbed water on the catalyst surface aer the reaction. With the developed catalyst, (1) aromatic alcohols are oxidized considerably faster than aliphatic alcohols, (2) benzyl alcohols with different functional groups (e.g., p-NO 2 , p-F, p-Cl, p-CH 3 , p-OCH 3 ) are fully air-oxidized to the corresponding aldehydes with $99% selectivity within 4 h of illumination, and (3) there is no over-oxidation to carboxylic acids, CO, or CO 2 in all cases.…”
Section: Surface Lattice Oxygenmentioning
confidence: 99%
“…Dai et al found that the O L -mediated selective photo-oxidation of alcohols over Bi 24 O 31 Br 10 (OH) d starts with the photo-dehydrogenation of alcohols to form adsorbed hydrogen species on the surface of the photocatalyst. 301 The O L of Bi 24 O 31 Br 10 (OH) d then oxidizes the alcohol to form aldehydes and OVs, and the OVs are subsequently healed by mild oxidants (O 2 or benzoquinone) to complete the photocatalytic cycle.…”
Section: Surface Lattice Oxygenmentioning
confidence: 99%
See 1 more Smart Citation